THE PROBLEMS OF DESIGNING: A PSYCHOLOGICAL AND PEDAGOGICAL DISCOURSE - Sukhenko, Yana (PSYCHOLOGICAL JOURNAL, 2020)
The article analyses theoretically the modern psychological and pedagogical researches on designing. The scientific research on this problem in psychology and pedagogy were systematized and put into the chronological order; the stages of dissemination of the ideas on designing, formation and development of psychological designing / self- designing and pedagogical designing were characterized. The general and specific ideas about these phenomena in each subject area are analyzed; the content and functional attributes of designing and self-designing, the features of psychological and pedagogical designing are defined. The pedagogical designing is specific because of: its focus on the development of innovative pedagogical systems of different scales, the development of educational environment and an educational space, on processes (educational, pedagogical, educational), the content of education and its forms; it basing on the principles of human priorities, self-development of the designed systems, characterized by dynamism, completeness, constructive integrity, and the possibility to be assessed; corresponding documenting with description of the history of creation and operations of designated objects; its research, analytical, prognostic, transformative, constructive functions; its representation with structural and dynamic components - forecasting, modeling, development, implementation, generalization of results. The psychological designing is characterized by the dialectical unity of designing with the aim to create a project for the development of another person (them) and to self-designing, focused on ideal modeling of oneself and one’s own development. Psychological designing is embodied not only in the projects of personality development, but also in narratives, myths, legends about oneself, in personal self-concepts and self-projects. The structural and dynamic components / stages of self-designing are: a proto-project, a landmark project, an event project, a life project, a project to change personal characteristics. The trends in the development of ideas about the content and dynamic patterns of designing as a special human activity are identified. There is a whole range of “measurements” of this phenomenon and its psychological modes in time and space: “individual – social”, “functional – intentional”, “unconscious – conscious” as a basis for multidimensional modeling. The prospects for the further development of designing and designing culture in psychology and education are determined in the direction of designing, reflecting meta-modern trends with the synthesis of designing and self-designing on the psychological and pedagogical planes.